Tobacco control : comparative politics in the United States and Canada - Studlar, Donley T. (Peterborough, Ont. : Broadview Press, 2002)
Tobacco Controlis the first book to compare the politics of tobacco control in the United States and Canada. It describes the course of tobacco control policy, both regulation and taxation, in each country, and on several different levels of government. In doing so it provides a broad overview, showing how policies are similar or different, how they have changed over time, and how the two countries have learned from each other. In recent years the two countries have paid closer attention to each other's policies, both through governmental and non-governmental organizations, and each has leapfrogged the policy initiatives of the other. Now the Tobacco-Free Initiative of the World Health Organization is bringing tobacco control policy to a global level, and both countries are deeply involved. This book is a revealing exploration and comparison of the development of North American policies and the influence these policies are having in the attempt to regulate a major international business in the interests of public health. Academics please note that this is a title classified as having a restricted allocation of complimentary copies. Restricted titles remain available to adopters and to academics very likely to adopt in the coming semester. Whenadoption possibilities are less strong and/or further in the future, academics are requested to purchase the title, with the proviso that UTP Higher Education will happily refund the purchase price if the book is indeed adopted.
IndexA -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z
Includes bibliographical references (pages 289-311) and index.
Print version record.
JSTOR
Keywords: Smoking -- Government policy -- Canada; Smoking -- Government policy -- United States; Tobacco use -- Prevention -- Government policy -- Canada; Tobacco use -- Prevention -- Government policy -- United States; Tobacco industry -- Canada; Tobacco industry -- United States; Tabagisme -- Politique gouvernementale -- Canada; Tabagisme -- Politique gouvernementale -- États-Unis.; Tabagisme -- Prévention -- Politique gouvernementale -- Canada; Tabagisme -- Prévention -- Politique gouvernementale -- États-Unis.; Tabac -- Industrie -- Canada; Tabac -- Industrie -- États-Unis.; POLITICAL SCIENCE -- Public Policy -- General; Smoking -- Government policy; Tobacco industry; Canada; United States